NETWOOD - Composite made of flax fiber fabric and thermally-modified beech veneers. Part 1: mechanical properties and orthotrophic behaviour - Richard Wascher; Helena Fink; Georg Avramidis; Wolfgang Viöl (Journal of Materials Research and Technology)
This study examines the mechanical and adhesive properties of a novel composite material comprising thermally-modified beech veneer flax fiber fabric, and melamine resin as a binder, whereby veneers and the flax fabrics of some sample variants were plasma pre-treated. The plasma treatment resulted in a significant increase in melamine resin uptake for the veneer and the flax fiber fabric. The incorporation of flax fibres into the composite structure has the effect of levelling the direction-dependent mechanical properties, thus reducing the orthotropic differences typically for wood and wood based products. The composite variants produced with untreated flax fibre and plasma pre-treated veneers exhibited the most reduced orthotropic differences in tensile strength and shear strength. The samples with plasma-treated veneer demonstrated the most favourable results in terms of fracture strength and delamination reduction. However, excessive melamine loading introduced brittleness and slightly reduced mechanical properties. The research results contribute to the development of high-performance and sustainable wood composites for structural use in outdoor applications.